Proceedings of the 2018 Workshop on Privacy in the Electronic Society 2018
DOI: 10.1145/3267323.3268950
|View full text |Cite
|
Sign up to set email alerts
|

Invisible Pixels Are Dead, Long Live Invisible Pixels!

Abstract: Privacy has deteriorated in the world wide web ever since the 1990s. The tracking of browsing habits by different third-parties has been at the center of this deterioration. Web cookies and so-called web beacons have been the classical ways to implement third-party tracking. Due to the introduction of more sophisticated technical tracking solutions and other fundamental transformations, the use of classical image-based web beacons might be expected to have lost their appeal. According to a sample of over thirt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Invisible pixels are extensively studied starting from 2001 [6,18,34,36,44]. Invisible pixels, called "web bugs" in previous works, were primarily used to set and send third-party cookies attached to the request or response when the browser fetches such image.…”
Section: Invisible Pixels Known As Web Bugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Invisible pixels are extensively studied starting from 2001 [6,18,34,36,44]. Invisible pixels, called "web bugs" in previous works, were primarily used to set and send third-party cookies attached to the request or response when the browser fetches such image.…”
Section: Invisible Pixels Known As Web Bugsmentioning
confidence: 99%
“…Ruohonen and Leppänen [44] studied the presence of invisible pixels in Alexa's top 500 websites. They showed that invisible pixels are still widely used.…”
Section: Invisible Pixels Known As Web Bugsmentioning
confidence: 99%
“…Web tracking is an "arms race" between trackers and tracker-blockers [8,37,41,57,63,67,77,102]. A number of methods can be used for third-party tracking: cookies [28]; fingerprinting [1]; tracking pixels [78]; and more [27].…”
Section: Online Tracking and Targetingmentioning
confidence: 99%
“…Our work is based on foundational techniques for analyzing web messages for various data tracking practices, such as browser fingerprinting [3,24,57], the use of tracking pixels [38,66], and the collection of location data [6]. Email addresses typed into forms can be collected by third party scripts even when people leave the site without submitting the form, which is especially concerning as email addresses are commonly used as identifiers for constructing profiles over time [69].…”
Section: Web Traffic Analysismentioning
confidence: 99%